2011
DOI: 10.1371/journal.ppat.1002422
|View full text |Cite
|
Sign up to set email alerts
|

IRGM Is a Common Target of RNA Viruses that Subvert the Autophagy Network

Abstract: Autophagy is a conserved degradative pathway used as a host defense mechanism against intracellular pathogens. However, several viruses can evade or subvert autophagy to insure their own replication. Nevertheless, the molecular details of viral interaction with autophagy remain largely unknown. We have determined the ability of 83 proteins of several families of RNA viruses (Paramyxoviridae, Flaviviridae, Orthomyxoviridae, Retroviridae and Togaviridae), to interact with 44 human autophagy-associated proteins u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
227
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(242 citation statements)
references
References 49 publications
7
227
1
1
Order By: Relevance
“…76 After HIV, TB is the lead ing infectious cause of death worldwide. Interestingly, HIV also manipulates autophagy to improve viral infec tivity, 77 and a common target of RNA viruses is IRGM . 77 Together, these findings underscore the importance of host autophagy in orchestrating successful antimicrobial responses to mycobacteria.…”
Section: Autophagy In Respiratory Infection and Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…76 After HIV, TB is the lead ing infectious cause of death worldwide. Interestingly, HIV also manipulates autophagy to improve viral infec tivity, 77 and a common target of RNA viruses is IRGM . 77 Together, these findings underscore the importance of host autophagy in orchestrating successful antimicrobial responses to mycobacteria.…”
Section: Autophagy In Respiratory Infection and Sepsismentioning
confidence: 99%
“…Interestingly, HIV also manipulates autophagy to improve viral infec tivity, 77 and a common target of RNA viruses is IRGM . 77 Together, these findings underscore the importance of host autophagy in orchestrating successful antimicrobial responses to mycobacteria. Reports have identifi ed cases of totally drug-resistant TB in India with fears that totally drug-resistant TB will spread worldwide.…”
Section: Autophagy In Respiratory Infection and Sepsismentioning
confidence: 99%
“…Nevertheless, Singh et al (13,14) showed that human IRGM stimulates autophagy and proposed that IRGM localized to mitochondria, aiding mitochondrial fission, an event that was suggested to be required for IRGM-mediated autophagic restriction of mycobacteria. In relation to viruses, Grégoire et al (15) generated two-hybrid-based protein interaction maps and found that human IRGM was highly targeted by RNA viral proteins (from HCV, measles virus, and HIV-1) and interacted with autophagy components, thereby suggesting that IRGM is manipulated for promotion of virus replication.…”
mentioning
confidence: 99%
“…Previous work has attributed the bacterial susceptibility in Irgm1-deficient mice to defective processing of bacteria-containing phagosomes in macrophages and other cells (5,15,(25)(26)(27). That reduced capacity to manifest IFN-␥-induced killing of S. typhimurium and Mycobacterium tuberculosis has been further linked to altered autophagic function in Irgm1-deficient macrophages (15,20,21,(27)(28)(29)(30). Impaired autophagy ostensibly leads to a reduced capacity to restrict bacterial growth, increased inflammation, and ultimately death of the host, although these linkages have not been formally established.…”
mentioning
confidence: 99%